Correction: Heparin-induced tau filaments are structurally heterogeneous and differ from Alzheimer's disease filaments. Issue 62 (20th July 2018) - Fichou, Yann; Vigers, Michael; Goring, Andrew K.; Eschmann, Neil A.; Han, Songi
Abstract : Correction for 'Heparin-induced tau filaments are structurally heterogeneous and differ from Alzheimer's disease filaments' by Yann Fichou et al., Chem. Commun., 2018, 54, 4573–4576.